(untitled) (Fiep Bulletin - online, 2015)
Objective: To investigate the incidence of elderly hypertensive patients with impaired functional capacity. Method: Field research, the descriptive type with quantitative approach. The study took place in the Pio X Basic Health Unit, District of Umari-CE. Participating in the study there were 46 elderly who fit the inclusion criteria. Data collection was performed from the completion of the socio-demographic data form and the evaluation form in daily living activities grounded in the Katz Formula, were analyzed using SPSS (version 21) described and presented in charts. The project was approved by the Committee of Ethics in Research from Santa Maria University (according to CAAE: 32362614.2.0000.5180. Results: The sample showed mostly female 60.9%, 67.4% are married, not living alone 91.3% and 95.7% have children. As for Katz formula 47.8% came as independent for all activities, followed by independent for all activities unless one 28.3%. Conclusion: The results showed that most of the elderly population is considered independent, but need a special look, that must be individual and directed to meet the needs of older people without taking from them the right to do for themselves what they are capable of performing alone. This indicates the need for further studies and preventive measures to reduce the decreased ability of activities of daily living.